2010
DOI: 10.1038/jid.2010.165
|View full text |Cite
|
Sign up to set email alerts
|

A Subpopulation of CD163-Positive Macrophages Is Classically Activated in Psoriasis

Abstract: Macrophages are important cells of the innate immune system, and their study is essential to gain greater understanding of the inflammatory nature of psoriasis. We used immunohistochemistry and double-label immunofluorescence to characterize CD163+ macrophages in psoriasis. Dermal macrophages were increased in psoriasis compared to normal skin and were identified by CD163, RFD7, CD68, LAMP2, Stabilin-1, and MARCO. CD163+ macrophages expressed C-lectins CD206/MMR and CD209/DC-SIGN, as well as co-stimulatory mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
224
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(256 citation statements)
references
References 53 publications
18
224
2
3
Order By: Relevance
“…31 CD163, usually known as a typical M2 marker and strongly expressed in the spindle-shaped macrophages of HIV-related Hodgkin lymphoma, was recently found to be expressed on a subset of M1-polarized macrophages. 32 The presence of necrotic foci, a unique feature in the HIV-related Hodgkin lymphoma cases in the present study, may point to a proinflammatory activity. Cassol et al 33 observed a significant increase in spindle-shaped cells after differentiation of monocytes into M1 compared with M2a differentiated macrophages.…”
Section: Discussionmentioning
confidence: 60%
“…31 CD163, usually known as a typical M2 marker and strongly expressed in the spindle-shaped macrophages of HIV-related Hodgkin lymphoma, was recently found to be expressed on a subset of M1-polarized macrophages. 32 The presence of necrotic foci, a unique feature in the HIV-related Hodgkin lymphoma cases in the present study, may point to a proinflammatory activity. Cassol et al 33 observed a significant increase in spindle-shaped cells after differentiation of monocytes into M1 compared with M2a differentiated macrophages.…”
Section: Discussionmentioning
confidence: 60%
“…88,[91][92][93][94][95][96][97][98][99] Our data show that intraperitoneal administration of the LNA-miR-21 inhibitor enhances Ly6C hi monocyte recruitment and M1 macrophage accumulation at an inflammatory site, suggesting miR-21-mediated suppression of M1 activities of these cells in vivo ( Figure 6). Further investigation of the roles of miR-21 targets in these processes and in enhancement of the LPS response downstream of the CSF-1R are needed to understand the underlying mechanisms involved.…”
Section: Discussionmentioning
confidence: 91%
“…TLR ligands induce miR-21 expression, 63,88 and increased miR-21 levels have been reported in several inflammatory conditions such as osteoarthritis, 89 ulcerative colitis, 90 cardiac muscle injury, 91 cardiac hypertrophy, 92 and psoriasis 93 as well as in H. pylori-induced gastric cancer 95 and the inflamed lungs of LPStreated mice. 95 Many of these conditions were associated with alterations in the M1/M2 macrophage polarization state, 93,96 thus leading to the hypothesis that miR-21 is an indicator of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…+ and CD163 + macrophages express CD206 in the skin of AD 40 and psoriasis patients 41 , respectively. We have demonstrated for the first time the presence of iNOS + and CD206 + macrophages in the skin of patients with psoriasis and AD.…”
Section: Discussionmentioning
confidence: 99%